2011
DOI: 10.1017/s0143385711000459
|View full text |Cite
|
Sign up to set email alerts
|

On the self-similarity problem for smooth flows on orientable surfaces

Abstract: On each compact connected orientable surface of genus greater than one we construct a class of flows without self-similarities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Weak mixing follows immediately from [31], as the class of IETs considered there includes all IETs of bounded type. Moreover, under the additional assumption that the base IET satisfies so-called balanced partition lengths condition, such flows are not partially rigid [21]. In Section 3 we show that for an IET this additional condition is equivalent to being of bounded type, thus making the proof of Corollary 1.5 complete.…”
Section: Main Results and Its Consequencesmentioning
confidence: 92%
See 2 more Smart Citations
“…Weak mixing follows immediately from [31], as the class of IETs considered there includes all IETs of bounded type. Moreover, under the additional assumption that the base IET satisfies so-called balanced partition lengths condition, such flows are not partially rigid [21]. In Section 3 we show that for an IET this additional condition is equivalent to being of bounded type, thus making the proof of Corollary 1.5 complete.…”
Section: Main Results and Its Consequencesmentioning
confidence: 92%
“…Definition 3.2 (cf. [21]). We say that the interval exchange transformation T = T π,λ has balanced partition lenghts whenever there exists c > 0 such that for any n ∈ N the following two conditions hold:…”
Section: Iets Of Bounded Typementioning
confidence: 99%
See 1 more Smart Citation
“…The following result shows that the discontinuities for iterations of IETs of periodic type are well distributed. Proposition 3.3 (see [22]). For every IET T of periodic type there exists c ≥ 1 such that for every n ≥ 1 we have…”
Section: Ergodicity Of Piecewise Linear Cocyclesmentioning
confidence: 99%
“…14 In [25] it is shown that on on each compact orientable surface of genus at least 2 there is a smooth (non-singular) non-self-similar flow. It is unknown whether these constructions are non-reversible.…”
Section: 2mentioning
confidence: 99%